2009
DOI: 10.1590/s1415-43662009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem hidrológica na bacia hidrográfica do Rio Aiuruoca, MG

Abstract: RESUMOA simulação do comportamento hidrológico de bacias hidrográficas consiste em uma das principais ferramentas na gestão dos recursos hídricos, devido à possibilidade de predição do regime fluvial. A bacia em estudo está localizada na região Alto Rio Grande, Sul de Minas Gerais, com área de drenagem de 2.094 km², constituindo uma das bacias fundamentais de drenagem para o reservatório da Usina Hidrelétrica de Camargos (UHE -Camargos/CEMIG). Neste contexto se objetivou desenvolver e aplicar um modelo hidroló… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 20 publications
3
31
0
12
Order By: Relevance
“…The years 1995 and 1996 were used as model warm-up period, since initial conditions were unknown. Warm-up period is aimed at stabilizing initial conditions of soil water (VIOLA et al, 2009;CIBIN et al, 2010), which was observed from second year of simulation (Figure 2). …”
Section: Subject Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The years 1995 and 1996 were used as model warm-up period, since initial conditions were unknown. Warm-up period is aimed at stabilizing initial conditions of soil water (VIOLA et al, 2009;CIBIN et al, 2010), which was observed from second year of simulation (Figure 2). …”
Section: Subject Descriptionmentioning
confidence: 99%
“…To evaluate model accuracy based on E NS coefficient, van LIEW et al (2007) classification was adopted and used by several authors (VIOLA et al, 2009;DURÃES et al, 2011, ANDRADE et al, 2013. According to this classification, E NS value = 1 means perfect fit data simulated by the model; E NS > 0.75 (model is suitable and good); 0.36 <E NS <0.75 model is satisfactory and <0.36 model is not satisfactory.…”
Section: Subject Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…O clima predominante dessa região é subúmido, com deficiência de água moderada no inverno, megatérmico (Sousa, 2016). A temperatura média anual é de 25 ºC, com precipitação média anual de 1.852 mm (Viola et al, 2012).…”
Section: Methodsunclassified